Prevalence and antimicrobial-resistant characterization of Bacillus cereus isolated from ready-to-eat rice products in Eastern China - Chen, Jiancai; Zhang, Junyan; Zhan, Li; Chen, Honghu; Zhang, Zhen; Huang, Cheng; Yue, Min (Frontiers in Microbiology, 2022)
Bacillus cereus is a major foodborne bacterial pathogen in the world, which can cause diarrhoea and emetic syndrome. This study aimed to reveal the quantitative prevalence of B. cereus in ready-to-eat (RTE) rice products in Eastern China, and to gain essential information on the genetic and antimicrobial-resistant potential of B. cereus isolates. 91 out of the 1071 samples were positive for B. cereus. The contamination level of B. cereus in 0.5 % of RTE rice product samples outnumbered 103 CFU/g. The number of B. cereus attained 105-106 CFU/g in one sample. The distribution patterns of virulence genes in B. cereus isolates were identified by PCR. 84.6% of the B. cereus isolates had at least one enterotoxin or emetic toxin gene. The predominant pattern was XXV, and 9.9% of isolates belonged to it and possessed one enterotoxin gene entFM. The occurrence rate of hblACD and nheABC was 36.3% and 47.3%, respectively. Antimicrobial susceptibility tests revealed a high resistance rate toward penicillin, and 23.1% of the isolates were multi-drug resistant. B. cereus isolates were genotyped by using ERIC-PCR, and a total of 89 genotypes were determined. The Hunter Gaston Discriminatory Index (HGDI) attained 0.9995. Genetic relationships analysis revealed that B.cereus isolates in Group A tended to carry hblA, hblC, hblD, nheA, nheB, and show resistance to penicillin/trimethoprim/sulfamethoxazole. Collectively, this study was helpful for updating the knowledge of the contamination status of B. cereus in RTE rice products in China.